HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN PERAWATAN DIRI PASIEN SKIZOFRENIA DI RS JIWA PROF. DR. MUHAMMAD ILDREM MEDAN TAHUN 2023 - Zebua, Lely Yusniar; Tampubolon, Lindawati F.; Derang , Imelda (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Schizophrenia is a mental disorder that causes patients to lose self-control, particularly in terms of self-care, such as personal hygiene, toileting, dressing, and eating-drinking. Family support is an important factor that can influence the independence of schizophrenic patients in carrying out self-care. This study aims to evaluate the relationship between family support and self-care independence of schizophrenic patients at Prof. Dr. Muhammad Ildrem Mental Hospital Medan. This study used a correlational design with a cross-sectional approach, involving 98 families of schizophrenic patients undergoing outpatient care. The research instrument was a questionnaire with a Likert scale to measure family support and patient independence levels. The analysis results showed that although family support was in the good category, there was no significant relationship between family support and self-care independence of schizophrenic patients (P Value = 0.785). These results indicate that patient independence is more influenced by treatment duration than family support.